Role of Autophagy in Male Reproductive Processes in Land Plants - Norizuki, Takuya; Minamino, Naoki; Ueda, Takashi (Frontiers in Plant Science, 2020)
Autophagy is a highly conserved system for degrading and recycling cytoplasmic components. The identification of autophagy-related (ATG) genes, required for autophagosome formation, has led to numerous studies using atg mutants. These studies have revealed the physiological significance of autophagy in various functions of diverse organisms. In land plants, autophagy is required for higher-order functions such as stress responses and development. Although defective autophagy does not result in any marked defect in the reproductive processes of Arabidopsis thaliana under laboratory conditions, several studies have shown that autophagy plays a pivotal role in male reproduction in several land plants. In this review, we aim to summarize information on the role of autophagy in male reproductive processes in land plants.